The Effectiveness of Patient Safety Cultural Training with Mirror Method and Case Study on Nurse Understanding About Application of Patient Safety at Hospital Pekanbaru - Awaliyah Ulfah Ayudytha Ezdha; Silvia Nora Anggreini; Dwi Elka Fitri (Talenta Publisher, 2019)
Quality development in hospitals has led to efforts to improve quality oriented towards patient safety. The purpose of this study was to compare what methods were most effective between lectures and case studies to improve nurses' understanding of the application of patient safety. The design of the research used is a mix method that is qualitative and quantitative. This research was carried out at Hospital in Pekanbaru with a sample of the study were all nurses who served at the hospital as many as 60 people. The results obtained from the study showed that the mean value of nurses 'understanding of patient safety habit after the lecture method training was 67.47 with a standard deviation of 8.320 while the mean value of nurses' understanding of the HABIT of patient safety after training in the case study method was 73.97 with a standard deviation of 6.835. The independent t test results obtained p value = 0.002. The results of this study are expected in addition to improving the understanding of nurses as well as the hospital can apply the most appropriate method so that the goals of the patient's safety goals are the quality of service can be achieved.